2003
DOI: 10.1074/jbc.m304026200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Native Mouse Zona Pellucida Proteins Using Mass Spectrometry

Abstract: The zona pellucida is an extracellular matrix consisting of three glycoproteins that surrounds mammalian eggs and mediates fertilization. The primary structures of mouse ZP1, ZP2, and ZP3 have been deduced from cDNA. Each has a predicted signal peptide and a transmembrane domain from which an ectodomain must be released. All three zona proteins undergo extensive coand post-translational modifications important for secretion and assembly of the zona matrix. In this report, native zonae pellucidae were isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
197
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(220 citation statements)
references
References 60 publications
22
197
1
Order By: Relevance
“…The only invariant residues within the ZP domain are eight conserved C residues (2, 4); apparently, the domain consists of two halves, one containing the first four C residues and the other containing the remaining C residues (7,8). This finding is supported by the fact that the sequence between the two groups of C residues can be glycosylated (7,8) and is susceptible to protease digestion (34), as expected for a solvent-exposed polypeptide fragment linking independently folded regions. Moreover, PLAC1 (35) and OOSP1 (36) are proteins whose N-terminal sequences share homology with the first half of the ZP3 ZP domain, including C residues 1-4 (Fig.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The only invariant residues within the ZP domain are eight conserved C residues (2, 4); apparently, the domain consists of two halves, one containing the first four C residues and the other containing the remaining C residues (7,8). This finding is supported by the fact that the sequence between the two groups of C residues can be glycosylated (7,8) and is susceptible to protease digestion (34), as expected for a solvent-exposed polypeptide fragment linking independently folded regions. Moreover, PLAC1 (35) and OOSP1 (36) are proteins whose N-terminal sequences share homology with the first half of the ZP3 ZP domain, including C residues 1-4 (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…1 A). Because the other 12 C residues of ZP3 are present as intramolecular disulfides in the extracellular portion of the protein (7,8), and because cytoplasmatic C residues can be important for assembly of transmembrane protein complexes (25, 26), we asked whether mutation of the C residue to an S residue would affect secretion and assembly of mouse ZP3. The mutant C413S protein was secreted and assembled to the same extent as wild-type ZP3; also, its secretion was unaffected in transfected cell lines (data not shown).…”
Section: The Tmd Of Zp Proteins Ensures Correct Localization For Assementioning
confidence: 99%
See 2 more Smart Citations
“…The zona pellucidae is an extracellular matrix surrounding mammalian eggs that blocks polyspermy and protects the developing preimplantation embryo (Boja et al, 2003). It has been reported that early implantation stage embryos from which the zona pellucida was removed developed into blastocysts by in vitro culture without feeders (Mintz, 1962).…”
Section: Discussionmentioning
confidence: 99%